(untitled) (Research, Society and Development, 2022)
Chemistry has several specific knowledge fields. Within these fields, different knowledge can be developed, for example, in organic, which has a field of Chemistry of natural products, which presents a wide variety of chemical compounds. These substances are synthesized from the secondary metabolism from living beings, these compounds have a function of facilitate the life (adaptation) and the perpetuation of their species. The present essay was developed through a literature review based on the use of natural products in the teaching of Chemistry combined with the different educational tools that were being explored and developed in the educational field. Regarding to identification of the essays published in national journals related to the subject, some researches carried out in stricto sensu graduate programs and more than 30 works carried out by different authors over 20 years were identified in the period between 1995 and 2021. We conclude that there has been an evolution in the researches over time with regard to the use of natural products for teaching chemistry, in new ways of teaching and learning in relation to the tools used for teaching chemistry and new researches in teaching science in an inclusive perspective.